2005
DOI: 10.1002/ejic.200500143
|View full text |Cite
|
Sign up to set email alerts
|

Design, Preparation and Characterization of the Adducts of the Bis‐Amido Cobalticinium Complex [CoIII5‐C5H4CONHC5H4N)2][PF6] with Fumaric and Maleic Acids

Abstract: The supramolecular hydrogen-bonded adducts obtained by treating the cationic bis-amido complex [Co III (η 5 -+ with fumaric and maleic acid are investigated and their modes of aggregation in the solid state are explored. It is shown that the bis-amido organometallic complex can be mono-and di-protonated in the reaction with the dicarboxylic acids, leading to the formation of complex,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2006
2006
2016
2016

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 72 publications
0
4
0
Order By: Relevance
“…The calculated N···F distances are ca. 0.2 Å shorter than those observed in hydrogen-bonded adducts of cationic transition metal complexes with PF 6 - anions. , The two PF 6 - units show a pseudo-octahedral geometry with the distance between P and the fluorine atom engaged in the hydrogen bonding interaction being significantly longer than the other P−F distances (1.77 vs 1.62 Å in the average). Structures with two cis -fluorine atoms of each PF 6 - unit pointing to the cofacial pair of trans pyrrole N−H groups were also theoretically explored for {H 4 TPP(PF 6 ) 2 }.…”
Section: Resultsmentioning
confidence: 82%
“…The calculated N···F distances are ca. 0.2 Å shorter than those observed in hydrogen-bonded adducts of cationic transition metal complexes with PF 6 - anions. , The two PF 6 - units show a pseudo-octahedral geometry with the distance between P and the fluorine atom engaged in the hydrogen bonding interaction being significantly longer than the other P−F distances (1.77 vs 1.62 Å in the average). Structures with two cis -fluorine atoms of each PF 6 - unit pointing to the cofacial pair of trans pyrrole N−H groups were also theoretically explored for {H 4 TPP(PF 6 ) 2 }.…”
Section: Resultsmentioning
confidence: 82%
“…Alternatively, the reactions could be conducted in neat amine. In this case the reactions were complete at 35…”
Section: Account Syn Lettmentioning
confidence: 99%
“…[15][16][17] Hydrazones (where R = H) can form supramo-lecular arrays in the solid state due to the presence of the protic NH 2 group available for hydrogen bonding, a feature which is being exploited in the crystal engineering field. [18][19][20][21][22][23] The ligands chosen for this study are shown in Figure 2, with the expectation of conveying different steric demands on the titanium(IV) centre and facilitating the formation of different arrays in the solid state. …”
Section: Introductionmentioning
confidence: 99%